2021
DOI: 10.29060/taps.2021-6-1/oa2227
|View full text |Cite
|
Sign up to set email alerts
|

Who is an effective clinical teacher from the perspectives of medical students and residents?

Abstract: Introduction: Almost all published literature on effective clinical teachers were from western countries and only two compared medical students with residents. Hence, this study aims to explore the perceived characteristics of effective clinical teachers among medical students compared to residents graduating from an Asian medical school, and specifically whether there are differences between cognitive and non-cognitive domain skills, to inform faculty development. Methods: This qualitative study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Incorporating culture is also suggested to encourage students to be adaptive and creative in learning about soft skills [32], [33]. It is also necessary for the teachers to embed the soft skills into their daily practice especially during interpersonal interaction as role model for the students [34].…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating culture is also suggested to encourage students to be adaptive and creative in learning about soft skills [32], [33]. It is also necessary for the teachers to embed the soft skills into their daily practice especially during interpersonal interaction as role model for the students [34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, methods to impart humanism must evolve along with students' level of medical training. A qualitative study conducted in Singaporean found that medical trainees at different stages of their training valued different types of teachers, preferring a didactic approach in their earlier years, in contrast to more rolemodelling and feedback once they step into clinical practice (Ooi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To perform effectively, they must possess speci c professional qualities such as professional knowledge, clinical expertise, effective communication, and the ability to serve as role models [16][17][18][19]. Based on various studies [20][21][22][23], clinical teachers must have adequate clinical knowledge, problem-solving skills, clinical reasoning skills, and expert psychomotor skills. Additionally, clinical teachers must have excellent leadership abilities, be trusted by their colleagues, be accountable for their actions, be mature and open-minded, have non-judgmental behavior towards medical students, be self-con dent, and be satis ed with them.…”
Section: Introductionmentioning
confidence: 99%